Boron removal from silicon by hydrogen assistant during the electromagnetic directional solidification of AlSi alloys. (21st May 2019) - Jiang, Weiyan; Yu, Wenzhou; Qin, Hong; Xue, Yang; Li, Chunmei; Lv, Xuewei
Abstract: Boron (B) removal from silicon (Si) by using an Ar-20% H2 gas mixture during the AlSi solvent refining was investigated. Electromagnetic directional solidification was employed to enrich the primary Si crystals in the melt and simultaneously drive the produced Bx Hy gas species to migrate out of the Si enrichment zone. Thermodynamic analysis shows that the formation of Bx Hy gas species by the reaction of dissolved boron [B] and dissolved hydrogen [H] in AlSi melt is feasible. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDS) analysis confirmed that the impurity carbon (C), oxygen (O), and B adhered to the wall of the gas cavity, indicating that B removal can be attributed to the migration of gas species. As the flow time of Ar-20% H2 gas mixture increased, the B removal fraction significantly increased, and a maximum value of 96.3% for B removal fraction was achieved when the flow time was 150 min. Finally, an overall process for producing solar grade silicon (SoG-Si) from metallurgical grade silicon (MG-Si) with the combination of ArH2 refining in AlSi solvent and vacuum directional solidification was proposed. Highlights: An efficient removal of B from Si by H-assisted refining is proposed. The mechanism of B removal by ArH2 gas mixture is clarified. The effect of H flow time on B removal is discussed. A low-cost process for producing SoG-Si from MG-Si is suggested.